2022
DOI: 10.3390/ijms23052638
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Biomarkers Associated with Chemotherapy-Induced AKI

Abstract: Acute kidney injury (AKI) is a life-threatening condition characterized by a rapid and transient decrease in kidney function. AKI is part of an array of conditions collectively defined as acute kidney diseases (AKD). In AKD, persistent kidney damage and dysfunction lead to chronic kidney disease (CKD) over time. A variety of insults can trigger AKI; however, chemotherapy-associated nephrotoxicity is increasingly recognized as a significant side effect of chemotherapy. New biomarkers are urgently needed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 218 publications
(281 reference statements)
0
5
0
Order By: Relevance
“…There are multiple mechanisms involved in this process. First, the mechanisms of drug-induced kidney injury are associated with oxidative stress, inflammation, DNA damage, and tubular karyomegaly or polyploidy in the pathogenesis of nephrotoxicity (31). DNA damage can activate cellular senescence via the NF-κB pathway, causing inflammation and fibrosis in the kidney and other tissues (32).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple mechanisms involved in this process. First, the mechanisms of drug-induced kidney injury are associated with oxidative stress, inflammation, DNA damage, and tubular karyomegaly or polyploidy in the pathogenesis of nephrotoxicity (31). DNA damage can activate cellular senescence via the NF-κB pathway, causing inflammation and fibrosis in the kidney and other tissues (32).…”
Section: Discussionmentioning
confidence: 99%
“…175 In particular, chemotherapy-associated nephrotoxicity is increasingly recognized as a significant side effect of chemotherapy. About 17.5% of cancer patients develop AKI, 176 and among them, cisplatin-induced AKI is widely studied due to this drug's long history as an ideal chemotherapeutic agent since 1978. Studies have demonstrated that the mechanism of AKI induced by cisplatin is related to its direct nephrotoxicity and oxidative stress.…”
Section: Nanozymes For Inflammatory Diseasesmentioning
confidence: 99%
“…These patients experience proximal tubular dysfunction, often manifested as Fanconi's syndrome, leading to progressive kidney impairment at a young age [ 90 ]. This condition is also observed in CKD secondary to ifosfamide [ 94 ] or other drugs used to treat pediatric tumors [ 95 ] as well as viruses integrating into the genome [ 96 , 97 ]. Similar to genetic mutations, these insults can affect the ability of the DNA to repair.…”
Section: Mechanisms Of Ckd Progression In Childrenmentioning
confidence: 99%
“…Collectively, chemotherapy and tubulointerstitial damage secondary to nephrotoxic drugs, AKI and congenital conditions can cause CKD in children [ 95 ] via TEC dysfunction suggesting that TEC may have a more prominent role in many different forms of CKD than previously thought, especially in children (Fig. 3 ).…”
Section: Mechanisms Of Ckd Progression In Childrenmentioning
confidence: 99%